967. Concordance of Antibiotic Prescribing with the Proposed American Dental Association Acute Oral Infection Guidelines within Veterans Affairs (VA) Dentistry - Carlsen, Daniel (Open Forum Infect Dis, 2019)
BACKGROUND: US dentists prescribe 10% of outpatient antibiotics. However, assessing the appropriateness of dental antibiotic prescribing has been challenging due to a lack of guidelines for common infections. In 2019, the American Dental Association proposed clinical practice guidelines (CPG) on the management of common acute oral infections for the first time. Our objective was to describe national baseline antibiotic prescribing for the treatment of irreversible pulpitis, apical periodontitis, and acute apical abscess prior to the release of the proposed CPG. METHODS: We performed a cross-sectional analysis of national VA data from January 1, 2017 to December 31, 2017. We identified cases of irreversible pulpitis, apical periodontitis, and acute apical abscess using ICD-10-CM codes. Patient demographics, facility location, medical conditions, dental procedure codes (“CDTs”), and diagnostic (ICD-10-CM) codes were extracted from the VA Corporate Data Warehouse. Antibiotics prescribed by a dentist within 7 days of a visit were included. Multivariable logistic regression identified variables associated with antibiotic prescribing for each infection. RESULTS: Of the 470,039 VA dental visits with oral infections coded, 25% of irreversible pulpitis, 41% of apical periodontitis, and 61% of acute apical abscess visits received antibiotics. Amoxicillin was prescribed most frequently. Although the median days’ supply was 7 days, prolonged use of antibiotics was frequent (9.2% of irreversible pulpitis, 17.8% of apical periodontitis, 28.7% of acute apical abscess received antibiotics for ≥8 days). Of the irreversible pulpitis visits with antibiotics prescribed, 20.0% received ≥2 antibiotics. Patients with high-risk cardiac conditions, prosthetic joints, and certain dental procedures were associated with receipt of antibiotics (table). CONCLUSION: Prior to the release of the ADA guidelines, 75.8% and 59.4% of irreversible pulpitis and apical periodontitis were concordant with proposed recommendations. These data identify opportunities to improve prescribing and serve as a benchmark for future outpatient antimicrobial stewardship efforts. Future work should assess definitive dental treatment and populations without access to oral health care. [Image: see text] DISCLOSURES: All Authors: No reported Disclosures.